A Platelet-Rich Plasma-Derived Biologic Clears Staphylococcus aureus Biofilms While Mitigating Cartilage Degeneration and Joint Inflammation in a Clinically Relevant Large Animal Infectious Arthritis Model - Gilbertie, Jessica M.; Schaer, Thomas P.; Engiles, Julie B.; Seiler, Gabriela S.; Deddens, Bennett L.; Schubert, Alicia G.; Jacob, Megan E.; Stefanovski, Darko; Ruthel, Gordon; Hickok, Noreen J.; Stowe, Devorah M.; Frink, Alexa; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The leading cause of treatment failure in Staphylococcus aureus infections is the development of biofilms. Biofilms are highly tolerant to conventional antibiotics which were developed against planktonic cells. Consequently, there is a lack of antibiofilm agents in the antibiotic development pipeline. To address this problem, we developed a platelet-rich plasma (PRP)-derived biologic, termed BIO-PLY (for the BIOactive fraction of Platelet-rich plasma LYsate) which has potent in vitro bactericidal activity against S. aureus synovial fluid free-floating biofilm aggregates. Additional in vitro studies using equine synoviocytes and chondrocytes showed that BIO-PLY protected these cells of the joint from inflammation. The goal of this study was to test BIO-PLY for in vivo efficacy using an equine model of infectious arthritis. We found that horses experimentally infected with S. aureus and subsequently treated with BIO-PLY combined with the antibiotic amikacin (AMK) had decreased bacterial concentrations within both synovial fluid and synovial tissue and exhibited lower systemic and local inflammatory scores compared to horses treated with AMK alone. Most importantly, AMK+BIO-PLY treatment reduced the loss of infection-associated cartilage proteoglycan content in articular cartilage and decreased synovial tissue fibrosis and inflammation. Our results demonstrate the in vivo efficacy of AMK+BIO-PLY and represents a new approach to restore and potentiate antimicrobial activity against synovial fluid biofilms.